PELATIHAN DIVERSIFIKASI OLAHAN IKAN UNTUK MENINGKATKAN NILAI EKONOMI MASYARAKAT PESISIR PANTAI AMPENAN - Cicilia, Siska; Basuki, Eko; Alamsyah, Ahmad (Jurnal Bakti Nusa, 2025)
Fish is a source of animal protein and has essential amino acids that the body really needs. One of the fish producing areas in Mataram City is Ampenan. The type of fish most often caught by fishermen is tuna. Fishermen in Ampenan generally only sell fresh and simply processed fish. To increase the economic value of fish, it is necessary to provide training on appropriate technology for fish processing. Several fish derivative products are prepared simply, such as meatballs and nuggets. Meatballs and nuggets are derivative products that people really like. Diversification of fish products aims to increase economic value, increase nutritional value, improve quality and extend the shelf life of fish. This training activity was carried out in Bintaro Ampenan Village involving two groups of fishermen. Based on the activity evaluation, there were many benefits for the training participants and further training was needed to develop fish into other products.